Incidence of cervical pain in bank workers of Jalalabad city Afghanistan - Samsoor Walizada; Farhad AwalKhail; Said Baha Karimi (Science and Education, 2024)
Neck pain is pain that starts in the neck and can be associated with radiating pain down one or both of the arms. Neck pain can be caused by a variety of conditions or diseases that affect any of the tissues in the neck, including nerves, bones, joints, ligaments, and muscles. The cervical spine, or neck portion of the spinal column, is made up of seven bones (C1-C7) that are divided from each other by intervertebral discs. During exercise, these discs allow the spine to move freely and function as shock absorbers. Up to 75% of individuals will have neck discomfort at some time in their lives. Bank workers face this problem due to their workplace in relation to computer use and prolonged hours of working. An observational study is done in 150 bank workers from different banks of Jalalabad city. Participants completed a well-tested questionnaire and data was analyzed by Ms office excel program. In analysis, neck pain is dependent variable and age, height and BMI are independent variables, Results shows that Male frequency in bank is 150 and percentage is 100 because according to our community female are not allowed by their families to work in bank. These findings show that neck pain may be associated with type of job, design of work station and job demand. (Hogg-Johnson S 2009, Ariëns GA 2002, Côté P 2004) The study aims to find the appearance of pain in the neck v among bank workers of different private and governmental banks also exploring association of different posture, work hours and different mode of setting with neck pain among Bank workers. All the findings of this study strongly supports the hypothesis that neck pain is common in bank workers and showed association with posture of setting, work hours, continuous working hours, type of chairs.